-6(2y-1)=3.6

Simple and best practice solution for -6(2y-1)=3.6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(2y-1)=3.6 equation:


Simplifying
-6(2y + -1) = 3.6

Reorder the terms:
-6(-1 + 2y) = 3.6
(-1 * -6 + 2y * -6) = 3.6
(6 + -12y) = 3.6

Solving
6 + -12y = 3.6

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + -12y = 3.6 + -6

Combine like terms: 6 + -6 = 0
0 + -12y = 3.6 + -6
-12y = 3.6 + -6

Combine like terms: 3.6 + -6 = -2.4
-12y = -2.4

Divide each side by '-12'.
y = 0.2

Simplifying
y = 0.2

See similar equations:

| 25.0139-7.481x=-1.1(x-8) | | 4x=15-5y | | -9p+21+16p=5(p+4)+3 | | 2x-11=38+9x | | -2m-6+8m=-4m-2+10m | | 6.5(1+0.495*1.2)=5.114+4.3*1.2 | | 3p+3(p+2)=6p+2 | | 6.5(1+0.945*1.2)=5.114+4.3*1.2 | | -2z-9=-2z-10+1 | | 6t-9=3(2t-4)+3 | | 4x+2(4+x)=3(2+5x) | | 618.5172=2*3.14*24.01+2*3.14*4.9*h | | 3.6x-1.2=.7(10-x) | | 6.5(1+0.495x)=5.114+4.3x | | 19694.08=2*3.14*196+2*3.14*14*h | | .3x=1.2+2.3x | | 64d^5-32d^2= | | 6x+1.5=4x-3 | | 0.4(x-10)+0.6x=1 | | Y+(3-5)=12 | | (5z+3)(8+z)=0 | | 7sec(x)=7 | | 33.33t=-.25 | | -16-3c=5c | | 8343.8592=2*3.14*17.64+2*3.14*4.2*h | | -15n+8n+34-4=-65 | | 0.3z-62.1=3z | | -.1a=0 | | 15n+8n+34-4=-65 | | 6x-8x+5=-2x+-4+7 | | 1965.7656=2*3.14*54.76+2*3.14*7.4*h | | 15q+13q+8q=180 |

Equations solver categories